PENGEMBANGAN MEDIA PEMBELAJARAN MOTIF TRADISIONAL ACEH MELALUI APLIKASI EDUKASI INTRAKTIF UNTUK SISWA KELAS III SD 57 BANDA ACEH - Dina Epriana; Fitriani; Zainal Abidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive educational application-based learning media containing Acehnese traditional motifs and to determine its validity and practicality in cultural arts learning for third-grade elementary school students. This research employed a research and development method consisting of needs analysis, media design, product development, and limited trials. The research subjects involved material experts, media experts, third-grade teachers, and students of SD Negeri 57 Banda Aceh. Data were collected through validation sheets, teacher and student response questionnaires, and documentation. The data were analyzed using descriptive statistics. The results showed that the developed learning media was categorized as highly valid and highly practical. The media effectively assists students in recognizing Acehnese traditional motifs in an engaging and understandable way, thereby increasing students’ interest and participation in learning activities